PENGARUH PINJAMAN DALAM KEMITRAAN UNTUK PENENTUAN HARGA PRODUK (PENYEBAB PENINGKATAN HARGA: A THEORETICAL VIEW) - Sukardi (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Products price, including those of agroindustry, keeps increasing constantly with no indication of stopping. By default, people comprehend the cause of price increase is attributable to inflation. In fact, the inflation is determined based on the price before and the price after increase. It implies that the price increase is the cause of inflation not vice versa.This article was intended to explore and analyze two types of financing system so as to formulate a mathematical expression as a basis to find the root of the cause of price increase. The comparison method and cause-and-effect were used to undertake the objective. Each of the two compared financing systems is modeled in order to extract necessary variables.The results show that the high price is due to the number of comprising elements of the price especially interest rate of the loan. Numerical example substantiates that the interest-bearing loan system forces business to set price to contain more variables in order to keep the business operating while the partnership system shows a significant contrast. Out of the findings the articleconcludes that the price increase will never be stopped until businesses(agroindustry) start implementing partnership financing system in place of interest-bearing. The article further infers that the inflation is absent from the causing factors of the price increase. Keywords: price increase, inflation, interest-bearing loan system, partnership system